The shades of the photovoltaic solar energy - Diego Germán Lamas (Perspectivas Metodológicas​)
We are living on a time where the sources of “conventional energies” are being demonized due to the effects the latter are having on our “environment” or the accidents suffered thanks to its exploitation, and we embrace the “renewable energies” easily and without judgement; without asking ourselves too many  questions or going beyond the basic.The search for quick and socially acceptable solutions or alternatives to the problems exposed, lead us not to bring out those negative things that new technologies may have, these solutions have a wide range of positive points compared to its conventional competitors; but hiding the negative points is not the way the latter should develop. This work highlights those weaknesses that photovoltaic solar energy presents, so that from an expanded perspective it allows us to demand, as human beings interested and involved in the future, the analysis of this type of technology and its projects to be deepened; so as not to be surprised by a negative impact that we know or deduce it may have today.